An aggressive case of sclerosing mucoepidermoid carcinoma with eosinophilia of thyroid: a case report - Eason, James R.; Allison, Robert (International Surgery Journal, 2017)
Sclerosing mucoepidermoid thyroid carcinoma with eosinophilia (SMECE) of the thyroid is a rare disease with approximately 50 cases reported worldwide. We describe SMECE of the thyroid affecting a 44 year old female and the first reported case of SMECE of thyroid in New Zealand. This case is of interest as the disease course was particularly aggressive with uncommon immunohistology. Our patient presented with a 4 month history of a painless swelling in her right upper neck. CT revealed a diffusely enlarged thyroid with infiltration of the trachea. A total thyroidectomy, tracheal resection and bilateral neck dissection was performed. Histology showed nests and cords of moderately sized epithelioid cells with prominent nucleoli, with focal glands and tubules. Immunohistology was performed. CK14 and epithelial membrane antigen staining was focally positive. The patient went on to receive chemo-radiotherapy. A CT scan later revealed metastasis to her lungs. She died 7 months from her diagnosis. Our case provides an example of aggressive SMECE of thyroid.